(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
In this interview, we explore the creative process of Hortência Moreira, a visual artist who transforms everyday urban life into works imbued with memory and identity. The conversation reveals how her practice develops through the observation of the city, the collection of images and objects, and careful attention to materials, time, and the memories they carry. Hortência shares how her series emerge and evolve, how she revisits previous works without repetition, and how her exploratory and recursive gaze establishes a continuous dialogue between city, material, and creation. The interview highlights the artist’s commitment to process, where planning, invention, and memory intertwine to generate discoveries and expand her artistic production.